2021
DOI: 10.1128/jvi.01928-20
|View full text |Cite
|
Sign up to set email alerts
|

The ESCRT-I Subunit Tsg101 Plays Novel Dual Roles in Entry and Replication of Classical Swine Fever Virus

Abstract: Classical swine fever (CSF) caused by classical swine fever virus (CSFV) is one of the highly contagious diseases of swine with high morbidity and mortality, that negatively affects the pig industry worldwide, in particular China. Soon after the endocytosis of CSFV, the virus makes full use of the components of host cells to complete its life cycle. Endocytosis sorting complex required for transport (ESCRT) system is a central molecular machine for membrane protein sorting and scission in eukaryotic cells that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 48 publications
1
21
0
1
Order By: Relevance
“…Fatty acid synthase (FASN) interacts with CSFV NS4B and facilitates the virus proliferation by regulating the formation of lipid droplets (LDs) [ 54 ]. Recently, tumor susceptibility gene 101 (TSG101) has been reported to promote CSFV replication by interacting with NS4B and NS5B to form replication complexes [ 55 ]. In current study, CSFV production was apparently improved by overexpression of RPLP1 ( Figure 4 ); in contrast, it was drastically diminished by recombinant lentivirus-mediated RPLP1 knockdown ( Figure 3 ), which indicated that RPLP1 could positively modulate CSFV propagation.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid synthase (FASN) interacts with CSFV NS4B and facilitates the virus proliferation by regulating the formation of lipid droplets (LDs) [ 54 ]. Recently, tumor susceptibility gene 101 (TSG101) has been reported to promote CSFV replication by interacting with NS4B and NS5B to form replication complexes [ 55 ]. In current study, CSFV production was apparently improved by overexpression of RPLP1 ( Figure 4 ); in contrast, it was drastically diminished by recombinant lentivirus-mediated RPLP1 knockdown ( Figure 3 ), which indicated that RPLP1 could positively modulate CSFV propagation.…”
Section: Discussionmentioning
confidence: 99%
“…Naturally occurring strains are non-cytopathic in cell culture [173,175,177]. Important factors in transmission and virulence include attachment to host cells, viral replication, immunomodulatory effects, and inhibition of cell apoptosis [178][179][180][181][182][183][184]. There are three distinct genotypes with three or four sub-genotypes [83,173,175].…”
Section: Classical Swine Fevermentioning
confidence: 99%
“…(3) Some host proteins can help CSFV enter cells. For example, Tsg101 participates in clathrin-mediated endocytosis of CSFV [68]; LamR is a cellular attachment receptor for CSFV [69]; Anx2 is a cellular membrane protein likely associated with CSFV entry [70]; Integrin β3 is membrane-bound signal mediator related to the CSFV infection [71]. Some members of the small Rab GTPase family are also involved in virus entry; Rab5, Rab7, and Rab11 are needed for caveola-dependent endocytosis of CSFV in porcine alveolar macrophages [62].…”
Section: Host Proteins Whose Function Defect Exert Anti-csfv Effectsmentioning
confidence: 99%